2012
DOI: 10.1093/mp/sss007
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Blue-Light-Dependent Phosphorylation, Degradation, and Photobody Formation of Arabidopsis CRY2

Abstract: Arabidopsis cryptochrome 2 (CRY2) is a blue-light receptor mediating blue-light inhibition of hypocotyl elongation and photoperiodic promotion of floral initiation. CRY2 is a constitutive nuclear protein that undergoes blue-light-dependent phosphorylation, ubiquitination, photobody formation, and degradation in the nucleus, but the relationship between these blue-light-dependent events remains unclear. It has been proposed that CRY2 phosphorylation triggers a conformational change responsible for the subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 39 publications
0
43
0
2
Order By: Relevance
“…Thus, it is generally accepted that photoactivated cry1 and cry2 transduce light signals to downstream components, primarily in the nucleus. Different from cry1 but similar to phys, photoactivated cry2 forms photobodies in the nucleus [56,64,65]. Photobody formation is closely correlated with cry2 function and degradation.…”
Section: Physiological Functions and Actions Of Cryptochromementioning
confidence: 95%
“…Thus, it is generally accepted that photoactivated cry1 and cry2 transduce light signals to downstream components, primarily in the nucleus. Different from cry1 but similar to phys, photoactivated cry2 forms photobodies in the nucleus [56,64,65]. Photobody formation is closely correlated with cry2 function and degradation.…”
Section: Physiological Functions and Actions Of Cryptochromementioning
confidence: 95%
“…Secondly, to demonstrate that the blue light-induced checkpoint activation was due to clustering of TopBP1 in photobodies, we used the mutated AtCRY2 (D387A) as a control. The D387A mutation in the FAD binding pocket completely eliminates FAD binding to AtCRY2 and photobody formation (8). We constructed AtCRY2(D387A)-GFP-TopBP1 (Fig.…”
Section: Specificity Of Protein-protein Interactions Within Atcry2mentioning
confidence: 99%
“…Among plant photosensory proteins, the red light receptor phytochromes (PHYs) are the most extensively studied with respect to photobody formation. More recently, it has been found that the blue light photosensory receptor cryptochrome (CRY) forms photobodies as well (8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A photon is absorbed by the N-terminal flavin binding domain and initiates a chemical reaction within the protein, which in turn triggers a conformational change. The resulting "lit" state renders the cryptochrome receptor accessible to interacting proteins that trigger photomorphogenesis and signaling, while at the same time exposing ubiquitination sites elsewhere on the protein that target cry2 for degradation (Zuo et al, , 2012. The current challenge in this field is to determine which of the known primary photoreactions occurring in isolated cryptochromes in vitro are required for the initiation of biological activity and photomorphogenesis in vivo.…”
Section: Introductionmentioning
confidence: 99%